Pengetahuan kesehatan reproduksi melalui penyuluhan dengan booklet pada siswa SMA - Mudita Sri Hidayah; Ermiyani Ermiyani (Health Sciences and Pharmacy Journal, 2023)
Counseling and learning, as well as media on reproductive health have not been conducted at Muhammadiyah Imogiri, Bantu Senior High School. The results of interviews with students at Muhammadiyah Imogiri, Bantul High School found that 8 out of 10 people could not define what reproductive health is. This study aims to determine the difference before and after counseling through booklet media on knowledge about reproductive health in adolescents at Muhammadiyah Imogiri, Bantul High School and is expected to be used as a basis for the development of reproductive health education by counseling to adolescents to overcome high adolescent reproductive health problems. This type of research is pre experimental design using one-group pretest-postest design. Data were collected using a questionnaire. The population in this study was all X and XI grade students at Muhammadiyah Imogiri, Bantul High School, totaling 71 students. Data analysis using paired sample t test total sampling technique with a total of 31 respondents. that is there is a difference before and after being given health counseling. Based on the results of the study after being given health counseling on reproductive health shows the presence of (p-value = 0.000 or P 0.05) then, H0 is rejected and Ha is accepted this is shown before being given counseling intervention using booklets the average knowledge of respondents has knowledge of 23.23 and the average after health counseling using booklets is 27.69 which means that there is an increase in average knowledge after reproductive health counseling through booklet media is 4.45. There is a difference in reproductive health knowledge before and after health counseling through booklet media for adolescents in class X IPA and X IPS at Muhammadiyah Imogiri, Bantul High School.